Experimental investigation of soil blended with lime and lignosulphonate - M.K, Soundarya; S, Bhuvaneshwari; Kumar.S, Prasanna (International Journal of Engineering and Technology, 2018)
The deterioration of the structures which are built on the expansive soils is due to its volume change behavior, due to the presence of Mont-morillonite minerals in soil. Hence this soil requires adequate stabilization before commencement of any construction activities. The stabili-zation phenomenon in which addition suitable additives completely alters the behavior of the soil by changing the basic properties and there-by increasing the bearing strength of soil. The choice of the additives depends on the ease and permanence of the stabilizing characteristics achieved for the expansive soil. In this paper, an attempt is done to evaluate the behavior of soil when blended with additives like saw dust ash, lime and lignosulphonate at varying blending ratio. The objective of the research work is to focus on the change in the plasticity charac-teristics by utilizing the industrial waste as additive due to its cementitious value, making it eco-friendly and reduction in cost. Lignosulpho-nate is a by-product of paper pulp industry, generated during the sulphite process. From the literature, the optimum percentage for stabilizing works for lime and lignosulphonate was found to be two to eight percent and one to three percent respectively. Basic Index properties and compaction characteristics test were determined for both virgin and treated soil. The additives decreased the plasticity index, causing ag-glomeration of clay particles involving pozzolanic reaction.Â